Foreign Direct Investment in an Emerging Economy: Exploring the Determinants and Causal Linkages - Diana Kombui; Richard Angelous Kotey (Academic Journal of Economic Studies, 2019)
The objective of the study was to examine the determinants of Foreign Direct Investment (FDI) from 1985 to 2015 in an emerging economy, Ghana. The study used a robust OLS regression and a Granger Causality Test to test for causal effects on a longitudinal data of thirty years. The study found, using a robust OLS regression model that, Natural Resource Endowment, Government expenditure, External debt and Infrastructure has significant predictive effects on FDI although the effect were more profound for natural resources and government expenditure. Using a granger causality approach, interest rate, Natural Resource endowment, Government expenditure, inflation, Infrastructure and international reserves were observed to granger cause FDI. The study recommends that policyholders and the government should also put in place measures that would maintain natural resources and spend on improving infrastructure and development as these attract foreign investments into the country.
Keywords: E43; E44; 330; FDI; Granger causality; Co-integration; Error correction model